Gingival microleakage in class II composite restorations using different flowable composites as liner: an in vitro evaluation - Neda Lotfi; Behnaz Esmaeili; Ghazaleh Ahmadizenouz; Ali Bijani; Hadi Khadem (Babol University of Medical Sciences, 2015)
Introduction: One of the main disadvantages of composites is marginal microleakage using flowable composites as a liner beneath composite restorations has been recommended to reduce microleakage. The aim of this study was to assess the microleakage of class II restorations with different flowable composites liners. Materials & Methods :45 extracted premolars teeth with class II cavity preparation (90 cavities) were divided into five groups and filled as follows: 1.control group: hybrid composite(Z250) 2. Z250+surefil SDR flow 3.Z250+filtek supreme xt flow composite 4.Z250+Grandio flow 5.Z250+Tetric flow. Mesial and distal cavities were filled using snowplow and layering technique, respectively. After that, the samples were immersed in 0. 5% fuchsin solution and sectioned. Gingival microleakage was then graded. Data were analyzed using Kruskal Wallis and Mann Whitney U test. Results: There was no significant difference between the snowplow and layering methods. Microleakage of Tetric flow and Grandio flow liners was significantly higher than the control group. Other flowable composites showed no significant difference in comparison with the control group. Conclusion: In the present study, the results indicated that the flowable composites were not effective on reducing gingival microleakage.